Adolescence in modern Irish history - Cox, Catherine 1970-; Riordan, Susannah 1968- (Palgrave Macmillan, 2015)
"This edited collection, the first publication to address the topic of adolescence in Irish history, consists of nine chapters which examine the experience of Irish young adults from the 'affective revolution' of the early nineteenth century to the emergence of the teenager in the 1960s. Based on new archival research and drawing on an extensive international literature, established and emerging scholars explore the social and economic, political and literary contexts in which adolescence emerged as a period of life and ask whether there was such a thing as a distinctively Irish adolescence"...
Keywords: Geschichte 1900-2000; Geschichte 1800-1900; Geschichte 1800-1970; HISTORY / Europe / Ireland; HISTORY / Modern / 19th Century; HISTORY / Modern / 20th Century; HISTORY / Social History; Geschichte; Gesellschaft; Adolescence -- Social aspects -- Ireland -- History; Young adults -- Ireland -- History; Teenagers -- Ireland -- History; Jugend; Heranwachsender; Europa; Irland; Ireland -- Social conditions -- 19th century; Ireland -- Social conditions -- 20th century; Konferenzschrift -- 2011 -- Dublin